Novel dalbavancin-PLLA implant coating prevents hematogenous Staphylococcus aureus infection in a minimally invasive mouse tail vein model - Kloss, Marlen; Moerke, Caroline; Woitschach, Franziska; Wulf, Katharina; Illner, Sabine; Schulz, Steffen; Pauker, Viktoria I.; Riedel, Katharina; Grabow, Niels; Ince, Hüseyin; Reisinger, Emil C.; Sombetzki, Martina (Frontiers in Bioengineering and Biotechnology, 2022)
Infective/bacterial endocarditis is a rare, life-threatening disease with a hospital mortality rate of 22.7% and a 1-year mortality rate of 40%. Therefore, continued research efforts to develop efficient anti-infective implant materials are of utmost importance. Equally important is the development of test systems that allow comprehensive evaluation of new materials performance. In this study, a novel anti-bacterial coating based on dalbavancin was tested in comparison to rifampicin/ minocycline, and the applicability of a recently developed tail vein mouse model was validated for testing the implant coatings. Small polymeric stent grafts coated with a poly-L-lactic acid layer and incorporated antibiotics were colonized with Staphylococcus aureus before implantation into the tail vein of mice. The main read out was the hematogenous spread of the bacteria and the local tissue reaction to the contaminated implant. For this purpose, colony forming units (CFU) in blood, spleen and kidneys were determined. Tail cross sections were prepared for histological analysis and plasma cytokine levels as well as expression values of inflammation-associated genes were examined. Both antibiotic coatings performed excellently preventing infection onset. The present study expands the range of methods for testing the anti-infectivity of cardiovascular implants and the spectrum of agents for effective surface coating.